Hubungan Antara Rule of Ten Terhadap Kejadian Komplikasi Pasca Labioplasty - Sukma Purnama Sidhi; Arya Tjipta Prananda; Ridwan Balatif (Faculty of Medicine, Universitas Andalas, 2021)
Objective: To determine the relationship between the use of the rule of ten on the occurrence of postoperative complications. Methods: This study is an analytic study with a cross-sectional design. Samples were taken from cleft lip patient medical records at Accuplast Hospital Medan from 2016 to 2018. The sample size was taken using the total sampling technique. Data taken in the form of gender, age, weight, hemoglobin levels and postoperative complications. The data that has been obtained is then analyzed using SPSS. Results: A total of 86 patients were included in this study. The majority of patients were male (55.8%), body weight above 4.5 kg (98.8%), patient age over 10 weeks (97.7%), and hemoglobin levels above 10 g/dL (96 ,5%). A total of 80 patients (93%) met the rule of ten criteria and 7 patients (8.1%) had postoperative complications. From the results of the Fischer exact test analysis, it was found that there was no significant relationship between the rule of ten and postoperative complications. Conclusion: In this study, there was no significant relationship between the rule of ten and the incidence of post-labioplasty complications